(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article discusses the changing impact of the latest scientific approaches in the field of digital education and pedagogy on teaching methods and the increase of interactivity in educational processes, the formation, interest and mastery of students, and the application of information in practice. information about.